ANALISA EAP DALAM PEMBUATAN MODEL SISTEM PENGADAAN OBAT BERBASIS ELEKTRONIK PADA APOTEK - Ade Supriatna (STMIK Mardira Indonesia, Bandung, 2015)
Currently in general that pharmacy drug procurement process is still paper-based. This mechanism takes the cost and time pretty much. The presence of information technology can make the job more efficiently. Internet technology can be a means of liaison between the organization / company. Electronic -based drug procurement (e -procurement) is closely related to the Business to Business (B2B), and this study focused discusses the internal organization of the pharmacy (buyer), and did not make an assessment of the readiness of the supplier (seller), meaning that the supplier is deemed to have ready with the support of information technology and information systems to implement B2B with Pharmacy. Enterprise Architecture Planning (EAP) is a framework for generating model (blueprint) information architecture. To complete the identification and documentation of business functions need other tools that use the Value Chain, Business System Planning, Work System Framework, and Business Process Modeling Notation. Architecture such information is useful to the organization / company as early preparations in implementation of e -procurement. Keywords: Enterprise Architecture Planning (EAP), Data Architecture, Application Architecture, Technology Architecture, Roadmap E -Procurement Abstrak Saat ini secara umum bahwa Apotek melakukan proses pengadaan obat masih berbasis kertas. Mekanisme ini butuh biaya dan waktu yang cukup banyak. Kehadiran teknologi informasi dapat membuat pekerjaan menjadi lebih efisien. Teknologi internet dapat menjadi alat penghubung antar organisasi/perusahaan. Pengadaan obat berbasis elektronik (e-procurement) ini erat kaitannya dengan Business to Business (B2B), dan penelitian ini difokuskan membahas dari sisi internal organisasi Apotek (buyer), dan tidak melakukan assesment terhadap kesiapan pemasok (seller), artinya pemasok dianggap telah siap dengan dukungan teknologi informasi dan sistem informasi untuk melaksanakan B2B dengan Apotek. Enterprise Architecture Planning (EAP) merupakan sebuah framework untuk menghasilkan sebuah model (blueprint) arsitektur informasi. Untuk melengkapi dalam identifikasi dan dokumentasi fungsi bisnis perlu tools lain yakni menggunakan Value Chain, Business System Planning, Work System Framework, Business Process Modelling Notation. Arsitektur informasi tersebut selanjutnya berguna bagi organisasi/perusahaan sebagai persiapan awal dalam penyelenggaraan e-procurement. Kata kunci : Enterprise Architecture Planning (EAP), Arsitektur Data, Arsitektur Aplikasi, Arsitektur Teknologi, Roadmap E-Procurement